Digoxin Use and Subsequent Clinical Outcomes in Patients With Atrial Fibrillation With or Without Heart Failure in the ENGAGE AF‐TIMI 48 Trial. Issue 7 (July 2017) - Eisen, Alon; Ruff, Christian T.; Braunwald, Eugene; Hamershock, Rose A.; Lewis, Basil S.; Hassager, Christian; Chao, Tze‐Fan; Le Heuzey, Jean Yves; Mercuri, Michele; Rutman, Howard; Antman, Elliott M.; Giugliano, Robert P.
Abstract : Background: Digoxin is widely used in patients with atrial fibrillation despite the lack of randomized controlled trials. Observational studies report conflicting results regarding its association with mortality, perhaps because of residual confounding by the presence of heart failure (HF). Methods and Results: In the ENGAGE AF‐TIMI 48 (Effective Anticoagulation With Factor Xa Next Generation in Atrial Fibrillation‐Thrombolysis in Myocardial Infarction 48) trial, clinical outcomes of patients with atrial fibrillation with and without HF were examined by baseline digoxin use during a median follow‐up of 2.8 years. HF was defined at baseline as prior or current clinical stage C or D HF. Of 21 105 patients enrolled, 6327 (30%) were treated with digoxin at baseline. Among patients without HF (n=8981), digoxin use (20%) was independently associated with sudden cardiac death (adjusted hazard ratio, 1.51; 95% CI, 1.10–2.08), with no significant interaction by age, sex, left ventricular ejection fraction, renal function, or concomitant medications ( P >0.05 for each). Consistent results were observed using propensity matching (adjusted hazard ratio for sudden cardiac death, 1.90; 95% CI, 1.36–2.65). Among patients with HF (n=12 124), digoxin use (37%) was associated with an increase in all‐cause death, cardiovascular death, sudden cardiac death, and death caused by HF/cardiogenic shock ( P <0.01 for each), but not with noncardiovascular death, stroke/systemic embolism, or myocardial infarction. Conclusions: In this observational analysis of patients with atrial fibrillation without investigator‐reported HF, digoxin use was significantly associated with sudden cardiac death. While residual confounding cannot be excluded, the association between digoxin use and worse clinical outcomes highlights the need to examine digoxin use, particularly when prescribed to control heart rate in patients with atrial fibrillation in a randomized trial. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00781391.